2012
DOI: 10.1089/thy.2011.0452
|View full text |Cite
|
Sign up to set email alerts
|

Density of Tumor-Associated Macrophages Correlates with Lymph Node Metastasis in Papillary Thyroid Carcinoma

Abstract: Background: Tumor-associated macrophages (TAMs) have recently been recognized as being important players in the tumoriogenesis of many cancers, including advanced thyroid cancer. However, a role in papillary thyroid carcinoma (PTC), the most prevalent thyroid cancer, has not been established. We hypothesized that TAMs also facilitate tumor progression in PTC. Methods: We investigated TAMs density in both benign thyroid lesions and PTC tumors by CD68 immunostaining. CD68-positive cell density was further associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 29 publications
(30 reference statements)
8
94
4
1
Order By: Relevance
“…Ryder et al (2008) first demonstrated that high density of macrophages was associated with poor clinical outcome in advanced thyroid cancer, while following data have shown conflicting results (Ryder et al 2008, Cunha et al 2012, Qing et al 2012, Fang et al 2014. Meanwhile, recent experimental studies have been more focused on the pro-tumorigenic roles of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryder et al (2008) first demonstrated that high density of macrophages was associated with poor clinical outcome in advanced thyroid cancer, while following data have shown conflicting results (Ryder et al 2008, Cunha et al 2012, Qing et al 2012, Fang et al 2014. Meanwhile, recent experimental studies have been more focused on the pro-tumorigenic roles of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In thyroid cancers, a few epidemiologic studies have shown that high TAM densities were associated with poor pathologic subtypes, bigger tumor size, or the presence of LN metastasis (Ryder et al 2008, Qing et al 2012. Recently, several studies have been demonstrated possible molecular mechanisms of macrophage actions in PTCs, such as CXCL8 (Fang et al 2014) or CSF1 (Ryder et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of the HRAS variant did not differ among PTC subtypes (P=0.95). There were no associations between the HRAS variant and age, sex, tumor size, encapsulation, multifocality/intrathyroidal spread, Tumor-Node-Metastasis stage (22), thyroid nodule status, Hashimoto history, BRAF mutation or PTC subtype (all P>0.05; Table III). There were significant differences in the number of BRAF mutations among the different subtypes (P=0.041; Table IV).…”
Section: Single-stranded Conformational Polymorphism Analysis (Sscp) mentioning
confidence: 96%
“…In addition, Csf-/-BRAF transgenic mice displayed a reduction in tumor growth. 14 Accordingly, TAMs purified from human PTC displayed a higher expression of IL-10 and CD206 compared to peripheral blood monocytes 71 and promoted invasiveness of TC cell lines in vitro through to the production of CXCL8/IL-8. 45 …”
Section: Immune Cells In Tc Microenvironmentmentioning
confidence: 99%